Divergent modulation of Rho‐kinase and Ca(2+) influx pathways by Src family kinases and focal adhesion kinase in airway smooth muscle - Shaifta, Yasin (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: The importance of tyrosine kinases in airway smooth muscle (ASM) contraction is not fully understood. The aim of this study was to investigate the role of Src‐family kinases (SrcFK) and focal adhesion kinase (FAK) in GPCR‐mediated ASM contraction and associated signalling events. EXPERIMENTAL APPROACH: Contraction was recorded in intact or α‐toxin permeabilized rat bronchioles. Phosphorylation of SrcFK, FAK, myosin light‐chain‐20 (MLC(20)) and myosin phosphatase targeting subunit‐1 (MYPT‐1) was evaluated in cultured human ASM cells (hASMC). [Ca(2+)](i) was evaluated in Fura‐2 loaded hASMC. Responses to carbachol (CCh) and bradykinin (BK) and the contribution of SrcFK and FAK to these responses were determined. KEY RESULTS: Contractile responses in intact bronchioles were inhibited by antagonists of SrcFK, FAK and Rho‐kinase, while after α‐toxin permeabilization, they were sensitive to inhibition of SrcFK and Rho‐kinase, but not FAK. CCh and BK increased phosphorylation of MYPT‐1 and MLC(20) and auto‐phosphorylation of SrcFK and FAK. MYPT‐1 phosphorylation was sensitive to inhibition of Rho‐kinase and SrcFK, but not FAK. Contraction induced by SR Ca(2+) depletion and equivalent [Ca(2+)](i) responses in hASMC were sensitive to inhibition of both SrcFK and FAK, while depolarization‐induced contraction was sensitive to FAK inhibition only. SrcFK auto‐phosphorylation was partially FAK‐dependent, while FAK auto‐phosphorylation was SrcFK‐independent. CONCLUSIONS AND IMPLICATIONS: SrcFK mediates Ca(2+)‐sensitization in ASM, while SrcFK and FAK together and individually influence multiple Ca(2+) influx pathways. Tyrosine phosphorylation is therefore a key upstream signalling event in ASM contraction and may be a viable target for modulating ASM tone in respiratory disease.